Tunable Porous Coordination Polymers for the Capture, Recovery and Storage of Inhalation Anesthetics. Issue 33 (19th May 2017) - Abrahams, Brendan F.; Dharma, A. David; Donnelly, Paul S.; Hudson, Timothy A.; Kepert, Cameron J.; Robson, Richard; Southon, Peter D.; White, Keith F.
Abstract: The uptake of inhalation anesthetics by three topologically identical frameworks is described. The 3D network materials, which possess square channels of different dimensions, are formed from the relatively simple combination of Zn II centres and dianionic ligands that contain a phenolate and a carboxylate group at opposite ends. All three framework materials are able to adsorb N2 O, Xe and isoflurane. Whereas the framework with the widest channels is able to adsorb large quantities of the various guests from the gas phase, the frameworks with the narrower channels have superior binding enthalpies and exhibit higher levels of retention. The use of ligands in which substituents are bound to the aromatic rings of the bridging ligands offers great scope for tuning the adsorption properties of the framework materials. Abstract : 3D Capture : The widespread use of a variety of inhalation anesthetics present significant environmental, health and economic challenges associated with their release into the atmosphere. The ability of a family of 3D framework materials containing square channels to capture and store a range of anesthetics is described.